Recent Breakthroughs and Advancements in NOx and SOx Reduction Using Nanomaterials-Based Technologies: A State-of-the-Art Review - Ali, Moazzam; Hussain, Ijaz; Mehmud, Irfan; Umair, Muhammad; Hu, Sukai; Sharif, Hafiz Muhammad Adeel (Nanomaterials (Basel, Switzerland), 2021)
Nitrogen and sulpher oxides (NOx, SOx) have become a global issue in recent years due to the fastest industrialization and urbanization. Numerous techniques are used to treat the harmful exhaust emissions, including dry, traditional wet and hybrid wet-scrubbing techniques. However, several difficulties, including high-energy requirement, limited scrubbing-liquid regeneration, formation of secondary pollutants and low efficiency, limit their industrial utilization. Regardless, the hybrid wet-scrubbing technology is gaining popularity due to low-costs, less-energy consumption and high-efficiency removal of air pollutants. The removal/reduction of NOx and SOx from the atmosphere has been the subject of several reviews in recent years. The goal of this review article is to help scientists grasp the fundamental ideas and requirements before using it commercially. This review paper emphasizes the use of green and electron-rich donors, new breakthroughs, reducing GHG emissions, and improved NOx and SOx removal catalytic systems, including selective/non-catalytic reduction (SCR/SNCR) and other techniques (functionalization by magnetic nanoparticles; NP, etc.,). It also explains that various wet-scrubbing techniques, synthesis of solid iron-oxide such as magnetic (Fe3O4) NP are receiving more interest from researchers due to the wide range of its application in numerous fields. In addition, EDTA coating on Fe3O4 NP is widely used due to its high stability over a wide pH range and solid catalytic systems. As a result, the Fe3O4@EDTA-Fe catalyst is projected to be an optimal catalyst in terms of stability, synergistic efficiency, and reusability. Finally, this review paper discusses the current of a heterogeneous catalytic system for environmental remedies and sustainable approaches.